2018
DOI: 10.1038/s41598-018-31662-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Blood Transfusion on Recurrence and Mortality Following Colorectal Cancer Resection: A Propensity Score Analysis of 4,030 Patients

Abstract: Whether blood transfusion exacerbates cancer outcomes after surgery in humans remains inconclusive. We utilized a large cohort to investigate the effect of perioperative blood transfusion on cancer prognosis following colorectal cancer (CRC) resection. Patients with stage I through III CRC undergoing tumour resection at a tertiary medical center between 2005 and 2014 were identified and evaluated through August 2016. Propensity score matching was used to cancel out imbalances in patient characteristics. Postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 31 publications
4
78
1
6
Order By: Relevance
“…24 Furthermore, it has been observed that modulation of the postoperative systemic inflammatory response with perioperative corticosteroids is associated with fewer postoperative complications and improved survival; however, these findings are yet to be confirmed in prospective trials. 8,9 Allogeneic blood transfusion in the perioperative period is widely thought to be negatively associated with shortterm postoperative outcomes and survival in patients undergoing surgery for cancer, with an older Cochrane review, 4 a recent large propensity score matched study of over 4000 patients, 25 and a very recent comprehensive meta-analysis 3 reporting this to be the case. However, two propensity score matched cohorts from a single group of researchers found no negative impact on survival in colon 26 or rectal cancer, 27 and a smaller recent observational study found no independent impact of blood transfusion on colorectal cancer recurrence when corrected for preoperative anemia.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, it has been observed that modulation of the postoperative systemic inflammatory response with perioperative corticosteroids is associated with fewer postoperative complications and improved survival; however, these findings are yet to be confirmed in prospective trials. 8,9 Allogeneic blood transfusion in the perioperative period is widely thought to be negatively associated with shortterm postoperative outcomes and survival in patients undergoing surgery for cancer, with an older Cochrane review, 4 a recent large propensity score matched study of over 4000 patients, 25 and a very recent comprehensive meta-analysis 3 reporting this to be the case. However, two propensity score matched cohorts from a single group of researchers found no negative impact on survival in colon 26 or rectal cancer, 27 and a smaller recent observational study found no independent impact of blood transfusion on colorectal cancer recurrence when corrected for preoperative anemia.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been associated with increased tumour proliferation, apoptosis and metastasis spread [27]. Studies in patients with colorectal cancer show a similar disruption of the immune response associated with blood transfusion that is thought to control cancer spread [28,29].…”
Section: Potential Causes Of Transfusion-induced Immunementioning
confidence: 99%
“…In colorectal cancer patients, perioperative administration of RBC transfusion was shown to increase all-cause mortality, cancer-related mortality, combined recurrence-metastasisdeath, postoperative infection and surgical reintervention (12). In a recent large cohort study of 4000 patients, perioperative RBC transfusion was associated with worse cancer prognosis after curative colorectal resection, independently of anemia status (13). The potential mechanism, transfusion related immunomodulation (TRIM), act primary by reducing the cellular immune response, but also increases the production of growth factors that can promote tumor proliferation and metastasis (14,15).…”
Section: Introductionmentioning
confidence: 99%